QUALITY OF YOGYAKARTA CITY RELIGIOUS MODERATION INDEX IN 2022: Study of Community Understanding After the Covid-19 Pandemic - -, Elicia Eprianda_Khairun Nisa_Lahfiz Safutra (Jurnal Moderasi, 2023)
The covid-19 pandemic has changed many of the fabric of people's lives in terms of carrying out worship and also traditions that are usually routinely carried out by the people of Yogyakarta. This impacts the lack of enthusiasm for one's participation in worship according to the beliefs of each religious follower. The pandemic changed a person's religious attitude as evidenced by people who were initially diligent in praying in mosques or Sunday worship becoming unable to anymore due to limitations by government regulations to prevent the transmission of covid-19. As an area that has various religious characteristics due to a large number of immigrants from outside Java, the city of Yogyakarta amateurs will be in a prolonged conflict that can cause division. Therefore, it is essential to understand religious moderation and mutual respect. This study uses a field survey method (field research) with a combination approach between quantitative and qualitative methods (Mixed method Research) in 8 districts in the city of Yogyakarta. This study aims to investigate how far the understanding and awareness of the community in moderating and tolerating religious diversity in the social environment affects the quality of community piety after covid-19. The results showed differences in the National moderation index in Indonesia with the moderation index in the city of Yogyakarta. Four indices are used as a measure in viewing Religious Harmony (KUB) in Yogyakarta showing the principle of diversity is quite high in the local community. Keywords: religious moderation, post covid-19, religious moderation index